Dehumanizing air travel: a scoping review on accessibility and inclusion of people with disabilities in international airports - Gotti, David; Morales, Ernesto; Routhier, François; Riendeau, Jonathan; Hadj Hassen, Ahmed (Frontiers in Rehabilitation Sciences, 2024)
IntroductionWorldwide, one in six individuals live with a disability. Many people continue to experience disabling situations, particularly when travelling. Travel can be an important part of the lives of many people, including people with disabilities. Barriers to accessing air travel can lead to a reluctance to travel for these potential passengers. As early as the flight planning stage, options to facilitate accessibility are limited. At airports, passengers must travel long distances in areas where navigation is complex, and accessibility limited. Furthermore, few aircraft are accessible. The travel experience can have adverse effects on the health of people with disabilities. Practices are sometimes not inclusive, not always available, and may not address the full spectrum of possible needs. The objective of this study is to provide a state of art on accessibility features available to people with disabilities in the busiest international airports.MethodsA scoping review of practices in airport accessibility was done. A search strategy was deployed in 4 databases (Avery index to architectural periodicals, Medline, CINAHL, and Web of science). The official websites of the 35 busiest airports were exhaustively consulted. All information regarding accessibility measures and inclusive services were extracted.Results31 scientific articles, out of 3,640 screened, and all extracted data from airports’ website were considered for synthesis. While efforts are made in major airports, there is a great inconsistency in accessibility features. Both facilitators and challenges are encountered by people with disabilities at every stage of air travel. These stages include journey planning; getting to and from the airport, obtain human assistance, navigate in the premises, check in, security screening, using facilities, boarding and disembarking, customs and immigration procedures, and luggage management.DiscussionServices need to be extensively planned, placing a significant burden on passengers. The disability-centric perspective disregard passengers’ unique needs and capabilities, leading to a sense of dehumanization. The complexity of airport organizations, shared responsibilities, limited communication, training challenges can deter accessibility initiatives and create discomfort during travel. This study is the first step of a broader project supported by Canadian Accessibility Standards, focusing on enhancing inclusive accessibility in Canadian airports.